The application of an escape room teaching method on the training for ICU new nurses: a quasi-experimental study - Qiulan Hu; Yangjuan Bai; Yuanxiang Mo; Rui Ma; Lan Ding; Ming Zhou; Yimei Zhang; Fang Ma (BMC Medical Education)
Abstract Background There is a severe shortage of intensive care nurses worldwide, and training a qualified ICU nurse is hard since it takes a very long time to accumulate the intensive care knowledge and skills needed. This study aimed to examine the effect of an escape room teaching method on teamwork attitudes and intensive care knowledge of ICU new nurses, their satisfaction with, and willingness to participate in escape room training. Methods A convenience sampling approach was utilized to enlist new nurses from April 2023 to March 2024 in China. ICU nurses with less than two years of experience in the First Affiliated Hospital of Kunming Medical University were involved in our study. Most of them were female (85.71%) with bachelor’s degrees (85.71%), and without escape room experiences (92.86%). Teamwork attitudes were collected through the TeamSTEPPS Teamwork Attitudes Questionnaire (T-TAQ) developed by the Agency for Healthcare Research and Quality (AHRQ); intensive care knowledge were collected by researchers-made online intensive care knowledge tests; satisfaction with escape room training, and willingness to participate in the escape room training were collected by researchers-made online questionnaires. Finally, the data were analyzed with SPSS v.26. Descriptive statistics, the paired samples test, the Wilcoxon signed-rank test, multivariate regression, and Pearson correlation were utilized for analysis. Results Fifteen groups of new nurses participated in the escape room training. For teamwork attitudes, there were significant differences in the mean T-TAQ total score (p < 0.001) and in the dimensions of teamwork (p < 0.001), leadership (p < 0.001), situation monitoring (p = 0.019), mutual support (p < 0.001), and communication (p < 0.001) before and after the escape room training. For the learning level, the mean intensive care knowledge scores were significantly different before and after the escape room training (p < 0.001). As for the reaction level, the satisfaction of ICU new nurses with the escape room training was high (9.23 ± 0.869), and the majority of them (95.24%) were willing to participate in the escape room training. Conclusion Implementing the escape room teaching method could promote teamwork attitudes and intensive care knowledge of ICU new nurses, and they were satisfied with and willing to participate in the escape room training. The key limitations in the study are the absence of a control group and data loss, and the results should be taken with caution. Our findings indicate that the escape room can be conducted in clinical practice learning for nursing and medical education settings with some props, and in ways of game playing, which doesn’t require expensive equipment and can be conducted conveniently, suggesting that escape room might be a promising method with cost-effectiveness value for nursing and medical education globally.